2021
DOI: 10.1002/slct.202101364
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dihydro[1,3]oxazine‐Fused Isoflavone and 4‐Thionoisoflavone Hybrids as Antibacterials

Abstract: A series of isoflavone functionalized 3,4‐dihydro‐1,3‐oxazine hybrids was synthesized in good to excellent yields through a Mannich‐type condensation cyclization reaction of 6‐chloro‐7‐hydroxy‐3‐(2‐methoxy‐phenyl)‐chromen‐4‐one or 6‐chloro‐7‐hydroxy‐3‐(2‐methoxy‐phenyl)‐chromene‐4‐thione with formaldehyde and primary amines. After spectroscopic characterization, these newly prepared hybrids were evaluated for their antibacterial activities against two of each Gram positive (Staphylococcus aureus and Bacillus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…At 37 °C and 120 rpm, the plates were incubated for overnight. After the completion of the incubation period, the growth was measured by using a Thermo Scientific Multiskan Go plate reader in terms of OD (optical density) at 600 nm [17,18] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 37 °C and 120 rpm, the plates were incubated for overnight. After the completion of the incubation period, the growth was measured by using a Thermo Scientific Multiskan Go plate reader in terms of OD (optical density) at 600 nm [17,18] …”
Section: Methodsmentioning
confidence: 99%
“…From this culture, approximately 10 5 cells/mL were taken and inoculated into molten nutrient agar medium, which was subsequently poured into 90‐mm diameter Petri plates. After solidification, sterilized 6 mm disks, made of Whatman paper and also 90‐mm in diameter, were carefully placed on the solid agar surface at appropriate distances [11,18,20] . Different concentrations of the test compounds, including 1/2 MIC, MIC, and 2 MIC, were applied to the disks using a stock solution of 10.24 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The 96-well plates were kept in an incubator shaker at 100 rpm for 24 h. The MIC was determined as the lowest concentration that prevented observable cell growth. All experiments were conducted with three biological triplicates [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The hemolytic activity of the compounds OX7 and OX11 was studied using human red blood cells ( h RBCs) . The procedures used to perform the hemolytic study were similar to those reported earlier …”
Section: Materials and Methodsmentioning
confidence: 99%
“…55 The procedures used to perform the hemolytic study were similar to those reported earlier. 56 % hemolysis was calculated from the following equation (eq 2).…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%